KETUHANAN DALAM KENA UPANISAD - Sujaelanto (Widya Aksara, 2019)
Upanisad is part of the Vedas. Upanisad book is the beginning of the history of the development of Hindu thought that contributes to the development of Hindu philosophy. There is a variable between upanisad and one other and there are things that are highlighted. In general, upanisad teaches about God, Spirit, Karma, Maya, and Awidya. Kena upanisad consists of 35 main sloka / mantra and 4 sloka as an ornament. Kena upanisad teaches about the nature of God as a controller, mobilizer, life-giver in every life that is dubbed as Brahman. Etah Brahman in Kena as expressed with his eyes, eyes, ears, breaths, thoughts. Belief in God subject to upanisad is Pantheism and Monism